Genome-wide identification of barley MCs (metacaspases) and their possible roles in boron-induced programmed cell death - (:unkn) unknown (SPRINGER, 2018)
Developmental processes and stress-induction activate many key proteins in plants such as metacaspase which regulate programmed cell death (PCD). In this study, identification of barley metacaspases and their possible roles upon boron (B)-induction was investigated by using in silico and wet-lab methods. Genome-wide analysis revealed that barley genome harbor ten metacaspases which divided into three groups: Type-I, -I* and -II. Segmental and tandem duplication contributed their expansion. Metacaspase-specific catalytic residues (His and Cys) were found to be altered in HvMC1, 2, and 4, in which His exchanged to Meth or Ala, critical for their activity and substrate selectivity. Cis-acting elements were found to be associated with three main processes: stress response, growth/development, and light response. Digital expression analysis from eight tissues revealed tissue specific metacaspase expressions. In addition, RT-qPCR analysis conducted in appropriate (50 A mu M) and excess-B (1 and-3 mM) conditions in different time points (3 and 10 days). Toxic level of B caused growth inhibition and chlorosis which appeared at the leaf tips. Also, PCD initiation was detected after 3 days of excess-B exposure. Digital expression and qPCR analysis agreed with each other that HvMC4 expression was significantly increased upon excess-B supplementation. In opposite, HvMC5 was down-regulated in the leaf zones which was another critical B-responsive gene in barley. Hence, HvMC4 and HvMC5 seem to have antagonistic effect during PCD regulation. These results can provide insights for metacaspase functionality in barley, not only limited for B-induction but also various kinds of PCD-causing conditions.
Keywords: Metacaspase; Programmed cell death; Boron stress; Boron tolerance; Barley; Genome-wide identification; LEAF SENESCENCE; TRANSCRIPTOME ANALYSIS; GENE-EXPRESSION; TOXICITY TOLERANCE; CYSTEINE PROTEASE; APOPTOSIS; L.; CITRUS; FAMILY; CASPASES